A case of concomitant subclavian steal syndrome and thoracic outlet syndrome - Akihiro Kageyama, MD; Taku Suzuki, MD, PhD; Yasuhiro Kiyota, MD, PhD; Noboru Matsumura, MD, PhD; Takuji Iwamoto, MD, PhD; Masaya Nakamura, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 59-year-old woman presented with dizziness and numbness of her left upper limb. Computed tomography (CT) angiography revealed an occlusion of the subclavian artery at its origin, leading to a diagnosis of subclavian steal syndrome. She was treated with percutaneous angioplasty and stenting; however, her symptoms did not improve. CT angiography of the arm in the elevated position revealed subclavian artery stenosis at the costoclavicular space, and the diagnosis was neurogenic thoracic outlet syndrome (TOS). First-rib resection was performed, and the symptoms disappeared immediately after surgery. TOS should be considered when symptoms persist despite subclavian steal syndrome treatment. Physical examination and CT imaging with the arm elevated aid in diagnosing TOS.